HUKUM PERFILMAN DI INDONESIA (Suatu Pengantar) - ella evrita (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2017)
Law Enforcement about the Film in Indonesia, based on Law No. 33/2009 has been done, where the parties involved in the film jointly conduct activities to enhance the role and business of the film that is, the government, film business actors and the public in general are directly involved in the cinema activities.Film Law in Indonesia can be seen, among others, in the case of, Rights and Obligations of the Community, Rights and Obligations of Civillians, Rights and Obligations of Film and Film Performers. All of them have been explicitly regulated in Law no. 33 of 2009 About the Film. In practice, that the protection of the public in this case the audience of the film industry becomes very important, even the public can make efforts to a film can not be circulated because it contains elements that conflict with religious norms and legal norms. But on the other hand also the community can not do anything if a film declared not escaped censorship by the Film Censorship Institute, but according to the film community is qualified and worth to watch.